Higher Education - Andrä Wolter (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
During the last five years higher education research in Germany seems to be in a significant upturn. This is a side effect partly of the obvious boom of empirical educational research in general and partly of the reform movement that has affected the German higher education system since middle of the 1990s. The demand for data in the field of higher education will increase considerably in future. The available data infrastructure for higher education research in Germany consists of two complementary main sources: on the one hand the official higher education statistics, on the other hand survey-based research. All in all, there are no serious or principle obstacles to access to the available data stock. Access in particular to some of the most important surveys could be improved by the establishment of a Forschungsdatenzentrum at HIS Hochschul-Informations-System. Furthermore, there are some deficiencies in the present data provision. New topics and demands of data provision have to be integrated into official statistics and survey based research -e.g. such issues as migration status, competencies, lifelong learning, quality of studies, institutional effects, international mobility, programs to promote younger scholars etc.. In particular there is a lack of panel designs. The very new National Education Panel Study (NEPS) will eliminate some but not all of these deficiencies.
Keywords: 330; Hochschulstatistik; Panel; Bildungsforschung; Deutschland